IDENTIFYING KEY COST DRIVERS IN SEISMIC DESIGN OF REINFORCED CONCRETE STRUCTURES IN MALAYSIA (Malaysian Journal of Civil Engineering, 2025)
The increasing awareness of seismic hazards in Malaysia has highlighted the urgent need for earthquake-resistant design in reinforced concrete (RC) buildings. While seismic provisions enhance structural resilience, they also raise construction costs, creating challenges for stakeholders. This study investigates the key cost factors influencing the adoption of seismic design in Malaysia using a qualitative approach. Semi-structured interviews with experts were analysed through thematic and content analysis, providing new insights into cost drivers from professional practice. Six main themes emerged: geotechnical factors and stakeholder/regulatory requirements were the most significant (23.91% each), followed by standards and codes (21.01%), feasibility costs (13.04%), structural and material detailing (9.42%), and innovative construction methods (8.70%). Results show that while innovative techniques were acknowledged, their adoption remained limited. This study provides practical insights in linking professional perspectives with coded frequency analysis, enabling a structured prioritization of seismic cost drivers. The findings highlight the need for early-stage geotechnical assessments, streamlined regulatory processes, and strategic integration of technology to balance safety and cost-efficiency. These insights provide practical guidance for policymakers, engineers, and contractors seeking sustainable approaches to seismic design in Malaysia